Morphological and Physiological Responses of Cymbopogon citratus and Pennisetum alopecuroides to Saline Water Irrigation - Haifeng Xing; Asmita Paudel; Julie Hershkowitz; Youping Sun (Horticulturae, 2025)
Reclaimed water provides a sustainable and economical alternative for landscape irrigation, but its elevated salinity can negatively impact sensitive plant species. This study evaluated the salinity tolerance of two widely used ornamental grasses, Cymbopogon citratus (lemon grass) and Pennisetum alopecuroides (fountain grass), under three electrical conductivity (EC) levels: 1.2 (control), 5.0, and 10.0 dS·m−1. Visual assessments over 62 days showed that both species maintained an acceptable appearance under saline conditions. C. citratus exhibited no foliar damage, with visual scores above 4.6 even at 10.0 dS·m−1, whereas P. alopecuroides showed slight leaf injury but retained a score of 3.9 or higher. Growth parameters, such as plant height, leaf area, and shoot dry weight, decreased significantly in C. citratus with increasing salinity, particularly at 10.0 dS·m−1, where reductions reached up to 51.1%. In contrast, P. alopecuroides maintained stable growth indices under salt stress, although leaf area and tiller number were notably affected at high EC levels. Both species accumulated substantial amounts of sodium (Na+) and chloride (Cl−); C. citratus showed more pronounced ion accumulation than P. alopecuroides. These findings suggest that both grasses are suitable for landscaping in saline environments, although they employ different physiological strategies to cope with salt stress.